Enhanced Preservation of Pig Cardiac Allografts by Combining Erythropoietin With Glyceryl Trinitrate and Zoniporide. Issue 7 (13th May 2013) - Watson, A. J.; Gao, L.; Sun, L.; Tsun, J.; Doyle, A.; Faddy, S. C.; Jabbour, A.; Orr, Y.; Dhital, K.; Hicks, M.; Jansz, P. C.; Macdonald, P. S.
Abstract Erythropoietin has a tissue‐protective effect independent of its erythropoietic effect that may be enhanced by combining it with the nitric oxide donor glyceryl trinitrate (GTN) and the sodium–hydrogen exchange inhibitor zoniporide in rat hearts stored with an extracellular‐based preservation solution (EBPS). We thus sought to test this combination of agents in a porcine model of orthotopic heart transplantation incorporating donor brain death and total ischaemic time of approximately 260 min. Pig hearts were stored in one of four storage solutions: unmodified EBPS (CON), EBPS supplemented with GTN and zoniporide (GZ), EBPS supplemented with erythropoietin and zoniporide (EZ), or EBPS supplemented with all three agents (EGZ). A total of 4/5 EGZ hearts were successfully weaned from cardiopulmonary bypass compared with only 2/5 GZ hearts, 0/5 CON hearts and 0/5 EG hearts (p = 0.017). Following weaning from bypass EGZ hearts demonstrated superior contractility and haemodynamics than GZ hearts. All weaned hearts displayed impaired diastolic function. Release of troponin I from EGZ hearts was lower than all other groups. In conclusion, supplementation of EBPS with erythropoietin, glyceryl trinitrate and zoniporide provided superior donor heart preservation than all other strategies tested.